2014
DOI: 10.1016/j.actbio.2014.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanoribbons elicit cell specific uptake and delivery via activation of epidermal growth factor receptor enhanced by human papillomavirus E5 protein

Abstract: Ligands such as peptides, antibodies or other epitopes bind and activate specific cell receptors, and are employed for targeted cellular delivery of pharmaceuticals such as drugs, genes and imaging agents. Herein, we show that oxidized graphene nanoribbons, non-covalently functionalized with PEG-DSPE (1, 2-distearoyl-sn-glycero-3-phosphoethanolamine-N[amino(polyethyleneglycol)]) (O-GNR-PEG-DSPE) activate epidermal growth factor receptors (EGFRs). This activation generates predominantly dynamin-dependent macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 50 publications
6
20
1
Order By: Relevance
“…Similar results in the study by Mullick Chowdhury et al showed that A549 cells had no uptake of graphene nanoribbons. 32 Jaworski et al also pointed out that graphene platelets did not enter into the cells. 33 Nevertheless, as seen from Figure 4 and panels B−D of Figure 5, plenty of GS deposited closely to or attached on the cell membrane (indicated by the yellow arrow), which could pose direct stimulations to the cells through the physical contact.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similar results in the study by Mullick Chowdhury et al showed that A549 cells had no uptake of graphene nanoribbons. 32 Jaworski et al also pointed out that graphene platelets did not enter into the cells. 33 Nevertheless, as seen from Figure 4 and panels B−D of Figure 5, plenty of GS deposited closely to or attached on the cell membrane (indicated by the yellow arrow), which could pose direct stimulations to the cells through the physical contact.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Outside the cell, MSNPs and WSNTs were observed on the cell membranes. However, cytoplasmic protrusions observed during micropinocytosis were seen only around the WSNT aggregates [37]. These observations suggest that WSNTs and MSNPs can enter the cells via different uptake mechanisms without affecting viability or differentiation potential of MSCs at concentrations up to 50 µg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Because C 16 and C 24 ceramides are native components of cellular membranes, we wanted to determine if they had an effect on the entry of O‐GNRs into cells. We have previously established that O‐GNRs are uptaken into HeLa cells via a macropinocytotic‐like, dynamin‐dependent mechanism that relies on activation of epidermal growth factor receptor (EGFR) (Mullick Chowdhury et al, ). This was determined using four different inhibitors of specific uptake pathways at non‐lethal concentrations: the dynamin inhibitor dynasore, the EGFR inhibitor gefitinib, the macropinocytosis inhibitor ethylisopropylamiloride (EIPA), and the caveolae‐mediated endocytosis inhibitor filipin.…”
Section: Resultsmentioning
confidence: 99%
“…We also wanted to determine if the loading of ceramide onto O‐GNRs would have a significant effect on their entry into cells. Previously we determined that O‐GNRs have a macropinocytotic‐like, dynamin‐dependent mechanism that relies on activation of EGFR (Mullick Chowdhury et al, ). Because ceramides are important components of cellular membranes, we wanted to determine if loading ceramides onto O‐GNRs would have an effect on their uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation